Membrane-associated transcription factor peptidase, site-2 protease, antagonizes ABA signaling in Arabidopsis - Zhou, Shun-Fan (The New phytologist, 2015)
© 2015 The Authors. New Phytologist © 2015 New Phytologist Trust.